The Influence of Advertising Attraction and Celebrity Endorser on Purchase Intention of Cosmetic Products - Taat Kuspriyono; Tengku Kespandiar; Helmi Ali; Hilarius Wandan; Wa Ode Nur Ainun (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
This study intends to examine how celebrity endorsing and advertising attraction affect customer interest in purchasing cosmetic products. This study is quantitative in nature. Using a purposive sample approach, 100 respondents made up the study's population. Interviews and questionnaires are two common data collecting methods. A Likert scale was used to assess the instruments used to collect data on the variables X1 (Ad Attractiveness), X2 (Celebrity Endorser), and Y (Purchase Intention). The findings of this study suggest that the factors of advertising allure and celebrity endorsers significantly influence consumer interest in making purchases. In the coefficient of determination test, the dependent variable (purchase intention) is influenced by 77% of the independent factors (advertising attractiveness and celebrity endorsement). While additional factors not included in this regression analysis may have an impact on as much as 23%.